Peirce's mathematical-logical approach to discrete collections and the premonition of continuity - Rebello Cardoso, Helio [UNESP] (Taylor & Francis, 2012)
According to Peirce one of the most important philosophical problems is continuity. Consequently, he set forth an innovative and peculiar approach in order to elucidate at once its mathematical and metaphysical challenges through proper non-classical logical reasoning. I will restrain my argument to the definition of the different types of discrete collections according to Peirce, with a special regard to the phenomenon called premonition of continuity (Peirce, 1976, Vol. 3, p. 87, c. 1897). © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: collection; continuity; logics; mathematics; Peirce; relation